Perancangan Dan Pembuatan Alat Pengontrol Lampu Menggunakan Internet Of Things (IOT) Berbasis Arduino Uno - Meyliana, Henni (Teknologi Rekayasa Jaringan Telekomunikasi, 2021)
The internet has also been attached to smartphones. Smartphone is a device capable of developing the Internet of Things (IoT). Smartphones function to connect to an internet network that is equipped with features in the form of sensors. In using IoT as a network infrastructure tool, it will be able to control and monitor a predetermined device in the form of an Arduino Uno. Arduino does not function as a microcontroller development that is connected to the internet, so that it can make it easier to use lights in everyday life. The open source operating system on an Android smartphone can be used as a material for designing a lamp controller using the internet of thins (IoT) based on Arduino Uno (Atmega328 microcontroller) and a relay as a switch. Therefore, in testing the tool using Arduino which has a time lag of 1 minute. For the use of the Arduino Uno program, a time delay of 5 seconds is also provided, while waiting for the serial command to move from one relay to another.